Seagrass diversity in Pulau Banyak, Aceh Singkil District, Indonesia - ERNIATI ERNIATI; YUDHO ANDIKA; IMANULLAH IMANULLAH; IMAMSHADIQIN IMAMSHADIQIN; ERLANGGA ERLANGGA; RAHMAD RAHMAD; TOHA ALI TAULADAN; FAUJIAH REZEKI SIREGAR; ANDIRA FITRI; GARA HASONANGAN RITONGA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Erniati, Andika Y, Imanullah, Imamshadiqin, Erlangga, Rahmad, Tauladan TA, Siregar FR, Fitri A, Ritonga GH. 2023. Seagrass diversity in Pulau Banyak, Aceh Singkil District, Indonesia. Biodiversitas 24: 6621-6628. Seagrass is a high-level plant where life activities are submerged in seawater. Currently, the seagrass ecosystem is threatened with destruction and disappearance. The extent of seagrass ecosystems globally was estimated to have declined by about 58%. The solution to this problem is to balance local communities' utilization of biological resources and biodiversity maintenance. The biodiversity aspect of seagrass is key to the sustainability of seagrass ecosystems. Banyak Island is one of the sub-districts in Aceh Singkil Regency, which consists of a cluster of small islands and has rich fisheries and marine potential, one of them is seagrass, where station 1 is Balong Island, Stasion 2 is Balong Island, Stasion 3 is Lamun Island and Stasion 4 is Rago-Rago Island. This study aimed to assess the diversity of seagrass beds, including seagrass species composition, density, percentage cover, and water quality that affect the existence of seagrass ecosystems. This study used a purposive sampling method with 3 transect lines spaced 50 m perpendicular from the shoreline to the sea. Each transect line has 5 plots with a distance of 10 meters measuring 50 x 50 cm2, and the water quality parameters were measured in situ. This research found 5 seagrass species, namely T. hemprichii, C. rotundata, E. acroides, S. isoetifolium, and H. ovalis. C. rotundata is the species with the highest density on Matahari Island, but seagrass diversity is low, and no species were dominant in the groups. The results of PCA analysis showed that the environmental factors that most influenced the pattern of seagrass distribution and density were nitrate, phosphate, and substrate. The conclusion revealed that seagrass diversity on Banyak Islands is relatively low.